Description and chemical composition of ferromanganese deposits from Trout Lake, northern Wisconsin - H Twenhofel; V E McKelvey; H F Nelson; D E Feray (PANGAEA, 1945)
Sediments were collected with Eckman and Petersen dredges from the bottom of Trout Lake, northern Wisconsin, at 221 stations. Sampling was done with a spud sampler at 32 stations, and core samples were obtained with a Jenkins and Mortimer and a Twenhofel sampler at 17 stations. The shore and offshore deposits of the shores of Trout Lake and the shores of the islands are described. Megascopic descriptions are given of the samples collected with the Eckman and Petersen dredges. Sediments on bottoms of about 10 meters or deeper are mainly gyttja, or crusts composed of mixtures of organic matter, ferric hydroxide, and some form of manganese oxide. The latter deposits are extensive. Detailed descriptions of some of the samples of sands are given, and generalizations respecting size and distribution are made. Tables showing quartiles, medians, and coefficients of sorting and skewness of the coarse sediments collected from the bottom are given in tables. Mechanical analyses of all fine sediments, mainly gyttja, were not made, as previous experience seems to have demonstrated that results have no sedimentational value. Organic matter of the gyttja was determined and also the percentages of lignin in the organic matter. Core samples are composed almost entirely of fine materials, mainly gyttja, and determinations were made on these samples in the same way as on the samples obtained with the Eckman and Petersen dredges. Studies of the core samples show that the fine sediments usually contain in excess of 90 per cent moisture and there is very little change in the moisture content from top to bottom of cores. A map shows the distribution of the iron and manganese deposits. These deposits were found to contain 10 to 20 per cent of organic matter, 11 to 16 per cent of metallic iron, and 12 to 30 per cent of metallic manganese. No stratification of any kind was found in any of the deep-water sediments of Trout Lake except in the iron and manganese crusts. Absence of stratification is considered to be due to the slow rate of deposition and the mixing of sediments by organisms which dwell in them. The data indicate that the rate of deposition in the deep waters of Trout Lake is of the order of 1 foot in 15,000 years.
Supplement to: Twenhofel, H et al. (1945): Sediments of Trout Lake, Wisconsin. Geological Society of America Bulletin, 56(12), 1099-1142, https://doi.org/10.1130/0016-7606(1945)56%5B1099:SOTLW%5D2.0.CO;2